The Investigation of the Pharmacokinetics of Two Enrofloxacin Preparations Following Parenteral Administration in Calves - Bideci, Gül Banu Çiçek; Kaya, Sezai (Acta Scientiae Veterinariae, 2018)
Background: Enrofloxacin is a bactericidal antimicrobial drug in the fluoroquinolone group, developed for use only in the veterinary field. It is effective against gram negative and gram positive bacteria, Mikoplazma, Rickettsia, Ehrlichia ve Chlamydia. Enrofloxacin is converted to several effective and ineffective metabolites including ciprofloxacin. Ten to fifty percent of the drug is eliminated via urine and bile in unmetabolized form. Enrofloxacin is used in all domestic animal including ruminant and winged animals. In calves, enrofloxacin finds utilization in the respiratory system infections, septicemia caused by colibacillosis and in cases of intestinal inflammation by oral and parenteral ways. There are around 1920 enrofloxacin preparations with different formulations in Turkey. Eight hundred fifty-five of these preparations are in the form of parenteral solutions that are ready for use. In this study, the pharmacokinetics of two enrofloxacin preparations that are used in calves were investigated. Materials, Methods & Results: Ten female calves (Jersey strain, 46-50 day-old) were included. The animals were taken to a separate environment 15 days in advance, and medication administration was restrained. Throughout the trial, the animals were fed with unmedicated feed. Calf growing feed, water, and hay were given freely as feed. They continued to be fed by 3 liters of milk twice a day. The study was reviewed by Ankara University Animal Trials Local Ethics Committee and approved with decision number 2007-7-17 and file number 2007-56. The calves were divided into two groups including five calves each. Reference drug and test drug were administered intramuscularly at a dose of 2.5 mg per kg to group 1 and group 2, respectively. Blood samples were taken before (0.0 min) and after the drug administration at 0.25, 0.5, 1, 2, 4, 8, 12, 18, 24 and 36th h. The method used by Anadon et al. was used for plasma enrofloxacin extraction and concentration. The chemicals, drugs, and solutions that were used in the study are acetonitrile, triethylamine, methanol, enrofloxacin (provided by Bayer Turk), reference drug (50 mg/mL injectable enrofloxacin, 20 mL per vial), test drug (100 mg/mL injectable enrofloxacin, 20 mL per vial). The pharmacokinetic variables were investigated after parenteral administration of reference and test drugs. The plasma concentration-time curve for each animal showed that enrofloxacin followed the two-compartment open model. There was statically significant differences in area under curve, absorption rate constant and absorption half-life between reference and test drugs (P < 0.05). However these differences were evaluated as insignificant from the point of clinical pharmacology. Peak plasma concentration was reached 0.8-1.2 h after the administration of both reference and test drugs. It was also seen that the drug concentration stayed above 0.5 µg/mL for approximately 4 h and decreases to 0.04 µg/mL at the 36th hour after administration. Discussion: The results obtained for both reference and test drugs in this study show that enrofloxacin is well absorbed from the gastrointestinal track. The drug concentration in plasma continues to be higher than 0.5 mg/mL during the first 24 h. The authors of this study think that the differences that were found in this study regarding pharmacokinetic variables are not significant regarding clinical pharmacology although some statistically significant differences were found. The results of this study imply that both reference and test drugs may be used interchangeably.